Stylistyka polska drugiej połowy XX wieku i początków XXI wieku - WOJTAK, MARIA (Stylistyka, 2025)
The cognitive situation in Polish stylistics during the period under review changed fundamentally. From a linguistic sub-discipline integrating textual research, stylistics transformed into a trans-discipline, and in fact, almost blended with such disciplines as textology, genology, and discourse studies. A characteristic feature of stylistics is the disproportion in the scope of research covering its various divisions. Studies and dissertations in the field of theoretical stylistics dominate, especially those concerning the basic concepts of the discipline, above all, the concept of style. There is also a significant number of studies on the concept of the discipline itself and its relations with related and neighbouring disciplines. Moreover, studies in the field of descriptive stylistics stand out in termsof quantity, especially those concerning the stylistic varieties of the Polish language: first artistic style, followed by colloquial, scientific, official, and religious styles. This body of work (including syntheses) is further enriched by stylistic descriptions of speech genres and analyses conducted from a discursive perspective. Historical stylistics has received considerably less attention, although methodological discussions and variously configured analyses form a substantial collection of monographs, dissertations, and scholarly articles on the history of Polish language varieties, selected speech genres, or individual texts from past centuries. The largest research gaps are found in the areas of practical (applied) and comparative stylistics. Researchers interested in stylistic issues therefore face ambitious tasks, developing theoretical foundations for the discipline and preparing a research programme to reorient the directions of stylistic development.